Mu-opioid receptor-dependent transformation of respiratory motor pattern in neonates in vitro - Gumnit, Maia G.; Watters, Jyoti J.; Baker, Tracy L.; Johnson, Sarah M.; Johnson, Stephen M. (Frontiers in Physiology, 2022)
Endogenous opioid peptides activating mu-opioid receptors (MORs) are part of an intricate neuromodulatory system that coordinates and optimizes respiratory motor output to maintain blood-gas homeostasis. MOR activation is typically associated with respiratory depression but also has excitatory effects on breathing and respiratory neurons. We hypothesized that low level MOR activation induces excitatory effects on the respiratory motor pattern. Thus, low concentrations of an MOR agonist drug (DAMGO, 10-200 nM) were bath-applied to neonatal rat brainstem-spinal cord preparations while recording inspiratory-related motor output on cervical spinal roots (C4-C5). Bath-applied DAMGO (50-200 nM) increased inspiratory motor burst amplitude by 40-60% during (and shortly following) drug application with decreased burst frequency and minute activity. Reciprocal changes in inspiratory burst amplitude and frequency were balanced such that 20 min after DAMGO (50-200 nM) application, minute activity was unaltered compared to pre-DAMGO levels. The DAMGO-induced inspiratory burst amplitude increase did not require crossed cervical spinal pathways, was expressed on thoracic ventral spinal roots (T4-T8) and remained unaltered by riluzole pretreatment (blocks persistent sodium currents associated with gasping). Split-bath experiments showed that the inspiratory burst amplitude increase was induced only when DAMGO was bath-applied to the brainstem and not the spinal cord. Thus, MOR activation in neonates induces a respiratory burst amplitude increase via brainstem-specific mechanisms. The burst amplitude increase counteracts the expected MOR-dependent frequency depression and may represent a new mechanism by which MOR activation influences respiratory motor output.